2021
DOI: 10.21037/atm-20-3899
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lipoprotein(a) and risk of coronary heart disease according to different lipid profiles in the general Chinese community population: the CHCN-BTH study

Abstract: Background: To evaluate the contributions of elevated lipoprotein(a) [Lp(a)] to the risk of coronary heart disease (CHD) in the general Chinese community population according to different lipid profiles. Methods: We recruited individuals aged over 18 years from the baseline survey of the Cohort Study on Chronic Disease of Communities Natural Population in Beijing, Tianjin and Hebei (CHCN-BTH) using a stratified, multistage cluster sampling method. Data were collected through questionnaire surveys, anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…Whilst absolute cutoffs may be beneficial for decision making within the clinic, a linear increase in atherosclerotic CVD risk has been observed with Lp(a) concentration, suggesting that even a modest increase in Lp(a) may be determinantal ( 23 ). Notably, within this study, the observation that no difference was found between low (<30 mg/dl) and elevated (30–50 mg/dl) Lp(a) in ACS risk differs from recent findings, where Lp(a) levels over 30 mg/dl contributed to an increased risk of coronary heart disease ( 44 ) and a linear relationship with both fatal and nonfatal cardiovascular risk ( 45 , 46 ). This may, in part, be due to the disparity in race between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Whilst absolute cutoffs may be beneficial for decision making within the clinic, a linear increase in atherosclerotic CVD risk has been observed with Lp(a) concentration, suggesting that even a modest increase in Lp(a) may be determinantal ( 23 ). Notably, within this study, the observation that no difference was found between low (<30 mg/dl) and elevated (30–50 mg/dl) Lp(a) in ACS risk differs from recent findings, where Lp(a) levels over 30 mg/dl contributed to an increased risk of coronary heart disease ( 44 ) and a linear relationship with both fatal and nonfatal cardiovascular risk ( 45 , 46 ). This may, in part, be due to the disparity in race between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, a large number of studies have demonstrated that Lp(a) plays an important role in the risk of CVD as primary prevention in the general people with different races, such as White, Black, Asian and mixed [3][4][5][20][21][22]. As for secondary prevention, the association between Lp(a) levels and the risk of subsequent CVEs has been recognized in the patients with established coronary artery diseases (CAD), even they were complicated with diabetes [6,7,19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lipoprotein(a) [Lp(a)] has been recognized as a novel independent risk factor for the incidence of CHD [3][4][5][6][7], which is consisted of a low-density lipoprotein-like particle and apolipoprotein B100, with apolipoprotein(a) [apo(a)], the characteristic protein of Lp(a), covalently binding to it via a disulfide binding [8]. Compositionally, Lp(a) shows higher pathogenicity compared with LDLcholesterol (LDL-C) in CHD due to the presence of apo(a), which is regarded as the major causative factor of atherosclerosis, thrombosis and inflammation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia: total cholesterol (TC) ≥6.2 mmol/L and/or triglyceride (TG) ≥2.3 mmol/L and/or high-density lipoprotein cholesterol (HDL-C) ≤1.0 mmol/L and/or low-density lipoprotein cholesterol (LDL-C) ≥4.1 mmol/L. 20 …”
Section: Design and Methodsmentioning
confidence: 99%